2022
DOI: 10.31289/jite.v5i2.6365
|View full text |Cite
|
Sign up to set email alerts
|

Image Classification of Autism Spectrum Disorder Children Using Naïve Bayes Method With Hog Feature Extraction

Abstract: Autism Spectrum Disorder (ASD) is a developmental disorder that affects a person's ability to communicate and interact socially. Every year, the number of people diagnosed with Autism Spectrum Disorder rises, necessitating early detection in order to limit the number of people affected and provide proper treatment. As a result, a system was developed in this study to detect Autism Spectrum Disorder in facial photos utilizing versions of the Nave Bayes approach and HoG feature extraction. HoG feature extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…In the previous study conducted by [15], the findings showed that the autistic classification model based on facial data using the Naive Bayes classification method with the assistance of HOG feature extraction achieved highly satisfying performance. In the study, the model was built using a total of 200 data, where 80% was used as training data and 20% as testing data.…”
Section: Discussionmentioning
confidence: 92%
“…In the previous study conducted by [15], the findings showed that the autistic classification model based on facial data using the Naive Bayes classification method with the assistance of HOG feature extraction achieved highly satisfying performance. In the study, the model was built using a total of 200 data, where 80% was used as training data and 20% as testing data.…”
Section: Discussionmentioning
confidence: 92%
“…Skor f1 menghitung hasil rata-rata yang seimbang dengan menggabungkan presisi dan daya ingat. Persamaan di bawah ini mengilustrasikan cara menghitung nilainilai ini, dengan TP, TN, FP, dan FN masing-masing mewakili true positive, true negative, false positive, dan false negative (Muhathir et al, 2022)…”
Section: E Evaluationunclassified
“…HOG feature extraction has also been used to identify plant species from leaf patterns using HOG feature extraction and the KNN method (Bao et al, 2020) (Krairina, N,. et al 2022) (Muhathir et al, 2022).…”
mentioning
confidence: 96%